Pengaruh Work Life Balance, Motivasi dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Perusahaan Perbankan Kota Malang - Zakiyah, Amany; Malikah, Anik; Wahyuningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract Acquiring, developing, and retaining top talent is essential for banking firms. Workers who are considered quality are able to get the job done well. Focusing on work-life balance, motivation, and the work environment may greatly enhance employee wellbeing, which in turn leads to high performance. Finding out how factors like work-life balance, intrinsic motivation, and the physical workplace affect productivity in the banking industry is the primary goal of this study. Quantitative methodologies are used in this study in conjunction with explanatory research. A total of eighty-seven people from Bank BSI and BTN Syariah participated in the survey. A questionnaire was used to gather data, which was then analyzed using SPSS 30 software. According to the findings, 1) Work-life balance significantly impacts employee productivity. 2) Employee performance is greatly impacted by motivation. Thirdly, workers' output is greatly affected by their workplace. Keywords: Work Life Balance, Motivation, Work Emvironment, Employee Performance